Dynamic Temporal and Tactile Cueing in Young Children With Childhood Apraxia of Speech: A Multiple Single-Case Design. - Grigos, Maria I.; Case, Julie; Ying Lu; Zhuojun Lyu (Journal of Speech, Language & Hearing Research, 2024)
Purpose: Childhood apraxia of speech (CAS) is a multivariate motor speech disorder that requires a motor-based intervention approach. There is limited treatment research on young children with CAS, reflecting a critical gap in the literature given that features of CAS are often in full expression early in development. Dynamic Temporal and Tactile Cueing (DTTC) is a treatment approach designed for children with severe CAS, yet the use of DTTC with children younger than 3 years of age has not been examined. Method: A multiple single-case design was employed to examine the use of DTTC in seven children with CAS (aged 2.5–5 years) over the course of 6 weeks of intervention. Changes in word accuracy were measured in treated words from baseline to posttreatment and from baseline to maintenance (6 weeks posttreatment). Generalization of word accuracy changes to matched untreated words was also examined. A linear mixed-effects model was used to estimate the change in word accuracy for treated and untreated words across all children from baseline to posttreatment and to maintenance. A quasi-Poisson regression model was used to estimate mean change and calculate effect sizes for treated and untreated words. Results: Group-level analyses revealed significant changes in word accuracy for treated and untreated words at posttreatment and maintenance. At the child level, six of seven children displayed medium-to-large effect sizes where word accuracy increased in an average of 3.4/5 words across all children. Each child displayed some degree of generalization to untreated targets, specifically for words with the same syllable shape as the treated words. Conclusions: These results demonstrate that DTTC can yield positive change in some young children with CAS. Key differences in each child’s performance are highlighted.